PERBANDINGAN HASIL PEMERIKSAAN RETIKULOSIT, HEMATOKRIT DARAH VENA K?EDTA DENGAN DARAH NATRIUM SITRAT - Evi Dwi Aprilia Suryani; Titik Sundari; Dheasy Herawati (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2022)
Reticulocytes are red blood cells that are young or immature, do not have a nucleus and derived from the normoblast maturation process in the bone marrow. Hematocrit is a measurement result that states the ratio of red blood cells to blood volume in percent. Objectives of this research are to determine the difference in reticulocyte and hematocrit results using K?EDTA venous blood and 3.2% Sodium Citrate. Examination using manual method (blood smear) on reticulocyte parameters and semi automatic hematology analyzer for hematocrit. The research subjects were 20 students of Universitas Maarif Hasyim Latif Sidoarjo. The results of the Paired T-test statistic for reticulocytes showed that the p value = 0.163 (?? 0.05) there was no difference in the results of K?EDTA blood and 3.2% Sodium Citrate blood with Wesgard QC there were 55% in the Wesgard range and 45% out of range Westgard QC. While the results of the hematocrit with the Wilcoxon statistical test showed a p value = 0.006 (?? 0.05), namely there was a difference in the hematocrit value of K?EDTA blood and moderate sodium citrate with Wesgard QC, the majority of NaCitrate blood HCT values were decreased, namely there were 18 respondents 90% below the standard K?EDTA value.